Zipf's law for cities in the regions and the country - Kristian Giesen; Jens Suedekum (Institute for the Study of Labor (IZA), 2009)
The salient rank-size rule known as Zipf's law is not only satisfied for Germany's national urban hierarchy, but also for the city size distributions in single German regions. To analyze this phenomenon, we build on the insights by Gabaix (1999) that Zipf's law follows from a stochastic growth process. In particular, Gabaix shows that if the regions follow Gibrat's law, we should observe Zipf at both the regional and the national level. This theory has never been addressed empirically. Using non-parametric techniques we find that Gibrat's law holds in each German region, irrespective of how regions are defined. In other words, Gibrat's law and therefore Zipf's law tend to hold everywhere in space.
urn:nbn:de:101:1-2009012356
Keywords: R11; O4; 330; City size distributions; city growth; Zipf's law; Gibrat's law; rank-size rule; Stadtgeographie; Stadtgröße; Räumliche Verteilung; Publikationsanalyse; Deutschland